2001
DOI: 10.1063/1.1347960
|View full text |Cite
|
Sign up to set email alerts
|

On the development of large-scale structures of a jet normal to a cross flow

Abstract: It is well known that vortex rings are the dominant flow structures in the near field of a free jet, and this has led many researchers to believe that they also occur in a jet in cross flow (JICF). Previous studies have postulated that these vortex rings deform and fold as they convect downstream, which culminates in the formation of vortex loops at both the upstream and the lee-side of the jet column. In this paper, we take a fresh look at the vortical structures of JICF in water by releasing dye at strategic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
73
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(94 citation statements)
references
References 38 publications
17
73
0
1
Order By: Relevance
“…Smith and Mungal [6] were able to corroborate this relationship in the near field of the jet for blowing ratios between 10 and 25. By scaling the data with the blowing ratio, Kamotani and Greber were able to account for different regimes associated with the blowing ratio (also equal to the square root of the momentum flux ratio).…”
Section: The Single Jicf: Unconfined Casesupporting
confidence: 61%
See 1 more Smart Citation
“…Smith and Mungal [6] were able to corroborate this relationship in the near field of the jet for blowing ratios between 10 and 25. By scaling the data with the blowing ratio, Kamotani and Greber were able to account for different regimes associated with the blowing ratio (also equal to the square root of the momentum flux ratio).…”
Section: The Single Jicf: Unconfined Casesupporting
confidence: 61%
“…Kelso, Lim, and Perry [5] studied various flow features of the JICF for a range of velocity ratios from 2-6 using hot-wire anemometry to examine the evolution of shear layer roll-up. Lim, New and Luo [6] then conducted a qualitative experiment on vortex formation by releasing a dye tracer at specific locations around the issuing jet. They found that the shear layer vortices that develop at the jet/crossflow interface coalesce as the jet propagates and eventually create the counterrotating vortex pair.…”
Section: Introductionmentioning
confidence: 99%
“…Similar large scale structures are known to exist even in low-speed JICF due to KelvinHelmholtz instabilities (KHI) (Fric and Roshko [2004]) of the vortex sheet created at the jet nozzle. These KHI occur along the windward and the lateral sides of the jet, forming a circumferential vortical structure rather than a vortex ring, as originally thought (Lim et al [2001]). …”
Section: Unsteady Features and Flow Dynamicsmentioning
confidence: 97%
“…Andreopoulos [1985], Yuan et al [1999], Lim et al [2001], New et al [2003]). Past experimental studies of JICF in supersonic crossflows have suggested that some of these vortical structures were also observed in supersonic JICF (VanLerberghe et al [2000], BenYakar et al [2006]).…”
Section: Chapter V Sonic Jet In Supersonic Cross-flowmentioning
confidence: 99%
“…The behaviour of these vortices depends on jet-to-crossflow velocity ratio, R = U j /U ∞ ; jet pressure, p j ; jet Reynolds number, Re dj = U j d j /ν j ; and jet pipe geometry [17]. Several authors [11,[18][19][20] have proposed different mechanisms for the development and evolution of jet shear-layer vortices in a subsonic crossflow. Smith and Mungal [21] observed that the formation of the jet shear-layer vortices is delayed in a subsonic crossflow with increased velocity ratios R > 5.…”
Section: Introductionmentioning
confidence: 99%